Changes in the Microanatomic Dimensions of the Femu in Chicken Postnatal Ontogenesis (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The dynamics of changes in the microanatomical dimensions of the femur of laying hens in postnatal ontogenesis was studied. It was established that the thickness of the proximal and distal epiphyses of the femur, dorsal and plantar compact substances increase up to 168 days, the thickness of the proximal and distal articular cartilages, the height and width of the medullary cavity increase up to 120 days of postnatal ontogenesis.